Evaluation of Plasmodium vivax HAP2 as a transmission-blocking vaccine candidate. Issue 13 (17th March 2020) - Qiu, Yue; Zhao, Yan; Liu, Fei; Ye, Bo; Zhao, Zhenjun; Thongpoon, Sataporn; Roobsoong, Wanlapa; Sattabongkot, Jetsumon; Cui, Liwang; Fan, Qi; Cao, Yaming
Highlights: Plasmodium vivax HAP2 protein was expressed in baculovirus for immunization. Transmission-reducing activity was evaluated with four P. vivax clinical isolates. Anti-PvHAP2 antibodies (Ab) significantly reduced infection intensity in mosquitoes. Anti-PvHAP2 Ab substantially reduced infection prevalence at low parasite exposure. Abstract: Transmission-blocking vaccine (TBV) is a promising strategy to interfere with the transmission of malaria. To date, only limited TBV candidate antigens have been identified for Plasmodium vivax . HAP2 is a gamete membrane fusion protein, with homology to the class II viral fusion proteins. Herein we reported the characterization of the PvHAP2 for its potential as a TBV candidate for P. vivax . The HAP2/GCS1 domain of PvHAP2 was expressed in the baculovirus expression system and the recombinant protein was used to raise antibodies in rabbits. Indirect immunofluorescence assays showed that anti-PvHAP2 antibodies reacted only with the male gametocytes on blood smears. Direct membrane feeding assays were conducted using four field P. vivax isolates in Anopheles dirus . At a mean infection intensity of 72.4, 70.7, 51.3, and 15.6 oocysts/midgut with the control antibodies, anti-PvHAP2 antibodies significantly reduced the midgut oocyst intensity by 40.3, 44.4, 61.9, and 89.7%. Whereas the anti-PvHAP2 antibodies were not effective in reducing the infection prevalence at higher parasite exposure (51.3–72.4 oocysts/midgut in the control group), the anti-PvHAP2 antibodies reduced infection prevalence by 50% at a low challenge (15.6 oocysts/midgut). Multiple sequence alignment showed 100% identity among these Thai P. vivax isolates, suggesting that polymorphism may not be an impediment for the utilization of PvHAP2 as a TBV antigen. In conclusion, our results suggest that PvHAP2 could serve as a TBV candidate for P. vivax, and further optimization and evaluation are warranted.